MRI Correlates of Ototoxicity in the Auditory Pathway in Children Treated for Medulloblastoma. Issue 1 (January 2022) - Moon, Peter; Theruvath, Johanna; Chang, Julia; Song, Yohan; Shpanskaya, Katie; Maleki, Maryam; Cheng, Alan G.; Ahmad, Iram N.; Yeom, Kristen W.
Abstract : Objective: To assess diffusion and perfusion changes of the auditory pathway in pediatric medulloblastoma patients exposed to ototoxic therapies. Study Design: Retrospective cohort study. Setting: A single academic tertiary children's hospital. Patients: Twenty pediatric medulloblastoma patients (13 men; mean age 12.0 ± 4.8 yr) treated with platinum-based chemotherapy with or without radiation and 18 age-and-sex matched controls were included. Ototoxicity scores were determined using Chang Ototoxicity Grading Scale. Interventions: Three Tesla magnetic resonance was used for diffusion tensor and arterial spin labeling perfusion imaging. Main Outcome Measures: Quantitative diffusion tensor metrics were extracted from the Heschl's gyrus, auditory radiation, and inferior colliculus. Arterial spin labeling perfusion of the Heschl's gyrus was also examined. Results: Nine patients had clinically significant hearing loss, or Chang grades more than or equal to 2a; 11 patients had mild/no hearing loss, or Chang grades less than 2a. The clinically significant hearing loss group showed reduced mean diffusivity in the Heschl's gyrus ( p = 0.018) and auditory radiation ( p = 0.037), and decreased perfusion in the Heschl's gyrus ( p = 0.001). Mild/no hearing loss group showed reduced mean diffusivity ( p = 0.036) in Heschl's gyrus only, with a decrease in perfusion ( p = 0.008). There were no differences between groups in the inferior colliculus. There was no difference in fractional anisotropy between patients exposed to ototoxic therapies and controls. Conclusions: Patients exposed to ototoxic therapies demonstrated microstructural and physiological alteration of the auditory pathway. The present study shows proof-of-concept use of diffusion tensor imaging to gauge ototoxicity along the auditory pathway. Future larger cohort studies are needed to assess significance of changes in diffusion tensor imaging longitudinally, and the relationship between these changes and hearing loss severity and longitudinal changes of the developing auditory white matter. Abstract : Supplemental Digital Content is available in the text